2015
DOI: 10.3389/fphy.2015.00075
|View full text |Cite
|
Sign up to set email alerts
|

Topological impact of constrained fracture growth

Abstract: The topology of two discrete fracture network models is compared to investigate the impact of constrained fracture growth. In the Poissonian discrete fracture network model the fractures are assigned length, position and orientation independent of all other fractures, while in the mechanical discrete fracture network model the fractures grow and the growth can be limited by the presence of other fractures. The topology is found to be impacted by both the choice of model, as well as the choice of rules for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…For every fracture that intersects the inflow boundary an edge is added between the vertex in the graph corresponding to that fracture and the vertex representing the inflow boundary; likewise for the outflow boundary. Similar graph theoretical approaches have been used for a variety of studies concerning DFN including topological characterization (Andresen et al, ; Huseby et al, ; Hope et al, ; Hyman & Jiménez‐Martínez, ) and backbone identification (Hyman et al, ; Valera et al, ). The utility of a graph theoretical approach is that topological properties of the networks can be queried and characterized in a formal mathematical framework.…”
Section: Flow and Transport Simulationsmentioning
confidence: 99%
“…For every fracture that intersects the inflow boundary an edge is added between the vertex in the graph corresponding to that fracture and the vertex representing the inflow boundary; likewise for the outflow boundary. Similar graph theoretical approaches have been used for a variety of studies concerning DFN including topological characterization (Andresen et al, ; Huseby et al, ; Hope et al, ; Hyman & Jiménez‐Martínez, ) and backbone identification (Hyman et al, ; Valera et al, ). The utility of a graph theoretical approach is that topological properties of the networks can be queried and characterized in a formal mathematical framework.…”
Section: Flow and Transport Simulationsmentioning
confidence: 99%
“…Using this mapping, or one that is similar, topological properties of the fracture network are inherited by the graph as measurable properties such as vertex degree, efficiency, clustering, betweenness, and community structure (Andresen et al, ). Various studies have used this mapping to characterize and study different aspects of fracture network structure in two‐dimensional (Andresen et al, ; Ghaffari et al, ; Santiago et al, ) and three‐dimensional (Aldrich et al, ; Hope et al, ; Hyman et al, ; Valera et al, ) networks (both synthetic and natural). Ghaffari et al () linked the sensitivity of flow properties in two‐dimensional networks, for example, flow field profiles, to the network structures.…”
Section: Topological Inquiriesmentioning
confidence: 99%
“…Andresen et al () used this mapping for quantitative comparisons between real fracture networks and models generating synthetic networks. Hope et al () showed how topological properties of the network, such as clustering (one measure of local connectivity), are related to the growth mechanism by comparing different methods for stochastic network generation. Sævik and Nixon () included topological properties of two‐dimensional fracture networks into analytic expressions for permeability to account for network structure.…”
Section: Topological Inquiriesmentioning
confidence: 99%
See 1 more Smart Citation
“…These graph mappings allow for a characterization of the network topology of both two-and threedimensional fracture systems, and moreover enable quantitative comparisons between real fracture networks and models generating synthetic networks. Vevatne, et al [51] and Hope, et al [19] have used this graph construction for analyzing fracture growth and propagation, showing how topological properties of the network such as assortativity relate to the growth mechanism. Hyman, et al [23] used graph representations of three-dimensional fracture networks to isolate subnetworks where the fastest transport occurred by finding the shortest path between inflow and outflow boundaries.…”
Section: Introductionmentioning
confidence: 99%